2022
DOI: 10.3390/ma15030827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxyapatite Nanoparticles and Nitrogen Plasma Treatment on Osteoblast Biological Behaviors of 3D-Printed HDPE Scaffold for Bone Tissue Regeneration Applications

Abstract: The need for the repair of bone defects has been increasing due to various causes of loss of skeletal tissue. High density polyethylenes (HDPE) have been used as bone substitutes due to their excellent biocompatibility and mechanical strength. In the present study, we investigated the preosteoblast cell proliferation and differentiation on the adding nano-hydroxyapatite (n-HAp) particles into HDPE scaffold and treating HDPE/n-HAp scaffolds with nitrogen (N2) plasma. The three-dimensional (3D) HDPE/n-HAp scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Moreover, the in vitro study showed a better ossification process on the surface with AN-treatment, supporting the in vivo study. Previous studies showed that pre-osteoblast cells, including MC3T3-E1 cells, need scaffolding to attach to the surface by their pseudopodium 42 , 43 . Additionally, they were known to migrate or transform differently depending on the surface characteristics 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the in vitro study showed a better ossification process on the surface with AN-treatment, supporting the in vivo study. Previous studies showed that pre-osteoblast cells, including MC3T3-E1 cells, need scaffolding to attach to the surface by their pseudopodium 42 , 43 . Additionally, they were known to migrate or transform differently depending on the surface characteristics 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that pre-osteoblast cells, including MC3T3-E1 cells, need scaffolding to attach to the surface by their pseudopodium. 42,43 Additionally, they were known to migrate or transform differently depending on the surface characteristics. 43,44 Accordingly, it was revealed that proper scaffolding was suitable for their attachment and viability, proliferation, and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…FDM is more dependable and cost-effective when producing customized objects compared to other 3D-printing techniques and can be used to create scaffolds with controllable aperture sizes and morphologies. 51,85…”
Section: D-printing Techniques For Bioceramic Scaffoldsmentioning
confidence: 99%
“…Many studies have shown that FDM-based scaffolds have excellent tunable mechanical and biochemical properties, which can be exploited for bone regeneration. 17,21,51,85 The degradable composite β-TCP scaffold formed using FDM exhibited excellent biological and mechanical properties, making it a promising candidate for bone tissue engineering. 21 However, the viscosity of the molten material and nozzle size limit the printing resolution as well as shape and precision of the objects produced by FDM compared to those produced by SLA.…”
Section: D-printing Techniques For Bioceramic Scaffoldsmentioning
confidence: 99%